ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BILANGAN BERPANGKAT DAN BENTUK AKAR KELAS X DI SMK N 2 BUKITTINGGI - Anisa Nurul Azhari; M. Imamuddin; Elianis Elianis (KOLONI, 2022)
Education is something that is very important for us to create quality human resources. With education it can make us mature individuals because education keeps us from being stupid and education gives us a lot of knowledge, skills, etc. According to Harahap and Poerkatja, education is an activity given by parents to bring up a sense of moral responsibility for all the actions they do. Mathematics is a symbolic language that is useful for expressing many things and is useful for making it easier for us to think. Mathematics is not only used to advance the human mind, but mathematics also has many learning objectives, such as: 1). To make it easier for us to understand mathematical design, 2). Using logic in solving patterns and characteristics, 3). Aims to solve various problems that include problem solving abilities, 4). Aims to communicate with symbols, tables, etc., 5). Aims to respect the benefits of mathematics in our lives. This research was conducted at SMK N 2 Bukittinggi with the aim of knowing the level of problem-solving ability of students in working on questions of exponential numbers and forms of roots. The research instruments used were observation and tests of mathematical questions on the material of starting numbers and roots. The sampling technique used for this research is simple random sampling. The subjects of this study were 35 students in Class X Culinary 1 at SMK N 2 Bukittinggi for the 2022/2023 academic year. Keywords: Solution to problem, mathematical, Rank Numbers.